THE RECEPTION OF GREEK TRAGEDY IN THE “OLD” AND THE “NEW” SOUTH AFRICA - Van Zyl Smit, B. (Akroterion, 2012)
Reception studies in Classics are, as Lorna Hardwick (2003:iii) remarks in the preface to her recently published survey, changing rapidly. They include the study of translations, adaptations and performances of ancient Greek and Latin texts. This article concentrates on the reception of only one genre of Greek literature in South Africa and cannot pretend to deal with it exhaustively. Nevertheless the examination of a substantial number of translations, adaptations and productions of Greek tragedies in this country in the twentieth century reveals a continuing fascination with these classics. It also discloses aspects of the social, cultural and political circumstances of the milieu in which they were reinterpreted.